An Evaluation on the Compliance to Safety Helmet Usage among Motorcyclists in Batu Pahat, Johor - Ambak, Kamaruddin; Hashim, H.; Yusoff, I.; David, B. (International Journal of Integrated Engineering, 2011)
This paper presents methods on how to determine the level of practice of usage of safetyhelmet among motorcyclist in Batu Pahat and to identify the target group who are most likelyto violate the safety helmet law among. A questionnaire study was carried out in urban andrural Batu Pahat. A total of 185 respondents were interviewed and the data was analyzed usingthe statistics. Six variables were found to be significant at percent level (p